MODEL KONSEPTUAL ARTS-BASED ENTREPRENEURSHIP LEARNING (ABEL) PADA PEMBELAJARAN KEWIRAUSAHAAN DKV SMK: KAJIAN LITERATUR - Kukuh Pribadi; Dwi Kusumawardani; Aprina Murwanti (Ars: Jurnal Seni Rupa dan Desain, 2026)
Pendidikan kewirausahaan di sekolah menengah kejuruan (SMK) berperan penting dalam menyiapkan lulusan yang tidak hanya siap kerja, tetapi juga mampu menciptakan peluang usaha, khususnya pada bidang desain komunikasi visual (DKV) yang menuntut kreativitas dan inovasi. Namun, pembelajaran kewirausahaan masih cenderung bersifat teoretis dan belum terintegrasi dengan proses kreatif siswa. Penelitian ini bertujuan untuk merumuskan model pembelajaran kewirausahaan berbasis seni yang kontekstual. Penelitian menggunakan pendekatan kualitatif dengan jenis kajian pustaka (library research) melalui analisis literatur ilmiah yang relevan. Data dianalisis menggunakan teknik analisis isi melalui tahapan reduksi, kategorisasi, sintesis, dan perumusan model. Hasil penelitian menghasilkan model Arts-Based Entrepreneurship Learning (ABEL) yang terdiri atas enam tahapan, yaitu Artistic Exploration, Idea Framing, Creative Production, Business Translation, Market Interaction, dan Reflection and Entrepreneurial Meaning. Model ini mengintegrasikan proses kreatif berbasis seni dengan praktik kewirausahaan dalam satu siklus pembelajaran yang berkelanjutan. Model ABEL direkomendasikan sebagai kerangka pembelajaran untuk mengembangkan kreativitas, keterampilan praktik, dan sikap kewirausahaan siswa secara integratif dalam konteks pendidikan vokasi.Kata kunci: pembelajaran kewirausahaan; arts-based learning; model pembelajaran; SMK; desain komunikasi visual—A Conceptual Model of Arts-Based Entrepreneurship Learning (ABEL) in Vocational Visual Communication Design Entrepreneurship Education: A Literature Review. Entrepreneurship education in vocational high schools (SMK) plays an important role in preparing graduates who are not only work-ready but also capable of creating business opportunities, particularly in the field of visual communication design (DKV), which demands creativity and innovation. However, entrepreneurship learning still tends to be theoretical and has not yet been integrated with students’ creative processes. This study aims to formulate a contextual arts-based entrepreneurship learning model. The research employs a qualitative approach in the form of a library research study through the analysis of relevant scientific literature. Data were analyzed using content analysis techniques through the stages of reduction, categorization, synthesis, and model formulation. The findings produced an Arts-Based Entrepreneurship Learning (ABEL) model consisting of six stages: Artistic Exploration, Idea Framing, Creative Production, Business Translation, Market Interaction, and Reflection and Entrepreneurial Meaning. This model integrates arts-based creative processes with entrepreneurial practice within a single, sustainable learning cycle. The ABEL model is recommended as a learning framework for developing students’ creativity, practical skills, and entrepreneurial attitudes in an integrative manner within the context of vocational education.Keywords: entrepreneurship learning; arts-based learning; learning model; vocational high school; visual communication design